Pertanggungjawaban Direksi dalam Kepailitan Perseroan Terbatas Menurut Hukum Positif Indonesia - Edwar Fransisko, Rendra (Magister Kenotariatan, Universitas Jambi, 2025)
This study aims to analyze the liability of the board of directors in the bankruptcy of a Limited Liability Company under Indonesian positive law, using the case of PT. Gunung Bara Utama as the focal point. The research employs a normative legal approach through statutory, conceptual, and case study analyses. The findings indicate that the directors’ liability in bankruptcy is explicitly regulated under Law Number 40 of 2007 concerning Limited Liability Companies and Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. Directors may be held personally liable if proven negligent or acting beyond their authority, causing losses to the company, creditors, or third parties. The PT. Gunung Bara Utama case demonstrates that weak internal oversight and violations of the fiduciary duty principle were significant factors contributing to the bankruptcy. This research recommends strengthening regulations by clarifying the duty of care standard and enhancing supervisory mechanisms over directors to prevent abuse of authority leading to bankruptcy.